Kinetics and Mechanism of Oxidation of Amoxicillin and 6-Aminopenicillanic Acid by Dichromate in Presence and Absence of Succinic Acid - Kulkarni, A.S.; Patel, N.T. (Asian Journal of Chemistry, 2016)
In the present studies we report the kinetics of oxidation of organic acids, such as amoxicillin and 6-aminopenicillanic acid by dichromate in acetic acid-water medium in presence and absence of succinic acid. The oxidising reacting species, HcrO4– and Cr2O72–, participate in the reaction. The effect of varying concentrations of [substrate], [oxidant], [H+], added neutral salt have been studied. The order of reaction with respect to [oxidant] and [substrate] has been found to be unity from the slope of plots log k vs. log [sub]. The rate of reaction increases with increase in pH of perchloric acid. Hammett's acidity function and activity of water have been studied. Effect of temperature has been studied. Activation parameters were computed. The plot of DH* vs. DS* is linear. The effect of dielectric constant of the medium indicates the reaction to be ion-dipole. The results of oxidation products have been identified.